LANGKAH-LANGKAH MENYUSUN MEDIA LKS IPA BERBASIS SAINS TEKNOLOGI MASYARAKAT - Hanifah, Maria; Adlani, Nazri (IAIN Takengon, 2022)
STM is one approach that can be used to improve scientific attitudes. This journal aims to find out: The steps for compiling the IPA media based on Community Science Technology (STM). This journal provides an overview for readers to understand the steps in compiling research developments in making LKS IPA media based on Community Science Technology. The instrument used in compiling STM-based science worksheets is the RnD method. The method that this journal presents in the form of this development method uses the stages of Research and Development (R&D) that adapts the 4D model. This research takes four 4D steps, namely Define, Design, Develop and Disseminate. The instrument used is a validation sheet, an observation sheet on the implementation of STM. The steps for preparing the Science Technology Community-Based Science LKS Media begin with the first Defining Phase which contains front end analysis, student analysis, task analysis, concept analysis, and learning objectives analysis. The second stage of the Design (Design), which contains the preparation of the benchmark reference test, the stage of selecting the media, choosing the format, and the initial design. The third stage is the Development Phase (Develop) containing the evaluation of the device followed by revision, and field testing. The last stage is the dissemination stage